Financial Innovation and Resilience: Transforming Zambian MSMEs through Microfinance and Public-Private Partnerships - Siame, Pethias; Chisenga, Raphael Prince Akeem (Journal of Emerging Markets and Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the unequivocal cornerstone of the Zambian economy, constituting over 70% of GDP and nearly 90% of national employment. However, their immense potential is critically constrained by perennial challenges, including acute financing gaps, pervasive low financial literacy, and pronounced vulnerability to external economic shocks. While there is evidence that existing literature acknowledges these challenges, there is a scarcity of in-depth, qualitative research exploring the synergistic role of financial innovation and public-private partnerships (PPPs) in building adaptive resilience within the Zambian MSME context. Grounded in Adaptive Resilience Theory, this paper provides a comprehensive investigation into how financial innovation encompassing microfinance, impact investing, and digital financial services, coupled with robust PPPs, can systematically bolster the resilience and transformative capacity of Zambian MSMEs. Employing a rigorous qualitative multiple-case study methodology, the research meticulously examines a selection of MSMEs that have successfully leveraged innovative financial mechanisms to navigate profound economic volatility. The analysis incorporates recent pivotal policy initiatives, such as the expanded Credit Guarantee Scheme, to highlight how strategic, multi-stakeholder reforms can effectively alleviate credit constraints. The findings of the present study make an original contribution by demonstrating that the integration of digital record-keeping, targeted financial literacy programs, and tailored credit products, delivered through strategic PPPs, significantly enhances MSMEs’ creditworthiness, operational efficiency, and shock absorption capabilities synergistically. The paper concludes with a set of pragmatic, actionable recommendations for policymakers, financial institutions, and private sector actors to collaboratively foster an inclusive, resilient, and future-ready MSME ecosystem in Zambia, poised for sustainable growth in the Industry 5.0 era.